2020
DOI: 10.1136/lupus-2019-000375
|View full text |Cite
|
Sign up to set email alerts
|

Associations of serum soluble Fas and Fas ligand (FasL) with outcomes in systemic lupus erythematosus

Abstract: ObjectiveFas/Fas ligand (FasL) and B cell-activating factor (BAFF) signalling have pivotal roles in SLE pathogenesis. We investigated the clinical associations of serum concentrations of soluble Fas (sFas) and soluble FasL (sFasL) in SLE and their relationship with BAFF.MethodsSerum sFas and sFasL were quantified by multiplex assay, and BAFF by ELISA, in 118 patients with SLE and 17 healthy controls (HC). SLE disease activity and organ damage were assessed using the Systemic Lupus Erythematosus Disease Activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…While in Sjögren's syndrome, the immune system targets mainly salivary and tear glands engendering dryness in the eyes and mouth, these diseases can affect other organs including skin, kidneys, articulations, lungs, and brain. In Lupus and SS, accumulating evidence points to s-CD95L as a pivotal effector of the disease aggressiveness [6,102], with a recent study confirming that s-CD95L levels were higher in lupus patients [103]. We previously observed that s-CD95L concentrations were associated with the disease progression in lupus patients, and that this ligand promoted the Th17 trafficking in inflamed organs [4,5].…”
Section: Lupus and Sjögren's Syndromementioning
confidence: 72%
“…While in Sjögren's syndrome, the immune system targets mainly salivary and tear glands engendering dryness in the eyes and mouth, these diseases can affect other organs including skin, kidneys, articulations, lungs, and brain. In Lupus and SS, accumulating evidence points to s-CD95L as a pivotal effector of the disease aggressiveness [6,102], with a recent study confirming that s-CD95L levels were higher in lupus patients [103]. We previously observed that s-CD95L concentrations were associated with the disease progression in lupus patients, and that this ligand promoted the Th17 trafficking in inflamed organs [4,5].…”
Section: Lupus and Sjögren's Syndromementioning
confidence: 72%
“…In addition, patients with more severe rheumatoid arthritis have higher sFASL levels in synovial fluid compared to those with less severe pathology [41][42][43] . These autoimmune diseases are all characterized by the presence of autoantibodies, produced by ASCs originating from self-reactive B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the ratio of sFas/sFasL has also been identified as a marker for vascular dysfunction or vasculopathy ( Adly et al, 2016 ). sFas and/or sFasL has been identified the association with tumor, coronary artery disease, rheumatic disease, and other diseases ( Sahinarslan et al, 2012 ; Adly et al, 2016 ; Chiloff et al, 2020 ; Vincent et al, 2020 ). However, the roles of sFas, sFasL and their ratio in PH with ESRD who undergoing hemodialysis (especially in elder patients) have not been identified.…”
Section: Introductionmentioning
confidence: 99%